2008
DOI: 10.1111/j.1399-0039.2008.01079.x
|View full text |Cite
|
Sign up to set email alerts
|

HLA‐A, ‐B and ‐DRB1 allele frequencies in the Bangladeshi population

Abstract: Population genetic studies have become an invaluable tool because of the extreme polymorphism found at some of the loci of the human leukocyte antigen (HLA) system. In this study, we are reporting for the first time the genetic polymorphism of 141 healthy unrelated Bangladeshi Bangalees living in central region of Dhaka. We studied the HLA-A, -B and -DRB1 loci using polymerase chain reaction with sequence-specific primers. The allelic frequencies, two and three locus haplotype frequencies were statistically an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
11
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 20 publications
1
11
2
Order By: Relevance
“…However, in a previous study from Bangladesh carried out among 141 samples, A11 was detected as the third highest frequent allele. 6 This variation of HLA A frequency between the present and previous study may be due to disproportion between the sample size of these two studies, as the earlier study was done on only 141 samples, while the present study had a much larger sample size of 1070. When compared with world population, A11 is found to be less frequent in Cuba, Argentina, Kenya and among Black and Hispanic ethnic regions.…”
Section: Discussioncontrasting
confidence: 43%
See 4 more Smart Citations
“…However, in a previous study from Bangladesh carried out among 141 samples, A11 was detected as the third highest frequent allele. 6 This variation of HLA A frequency between the present and previous study may be due to disproportion between the sample size of these two studies, as the earlier study was done on only 141 samples, while the present study had a much larger sample size of 1070. When compared with world population, A11 is found to be less frequent in Cuba, Argentina, Kenya and among Black and Hispanic ethnic regions.…”
Section: Discussioncontrasting
confidence: 43%
“…25 In this neighboring region in Siliguri (West Bengal), the two locus haplotype analysis revealed that A1-B37, A1-B40, A29-B40, A30-B51 and A31-B40 were the most frequent haplotypes. 26 In a previous study in Bangladesh, A33-B44 was found to be the most frequent allele, 6 but this was observed as the sixth frequent allele in our study. Thus, the two locus haplotypes A11: B75 revealed that the Bangladeshi population belongs to the Asian population and is most closely related to Oriental groups than to European groups.…”
contrasting
confidence: 47%
See 3 more Smart Citations